New Directions and New Partnerships - Wolfensohn, James D. (2016)
James D. Wolfensohn, President of the World Bank Group, addressed the annual meetings of the World Bank and the International Monetary Fund. He discussed the context in which the Bank operates today; the role of the Bank in development now, and in the coming years; what the Bank can do to achieve its objectives in an effective and accountable manner; and the Bank’s immediate and early initiatives. He called for a new IDA compact. The problem of debt overhang continues. He focused on the power of partnerships. He mentioned the need to develop an institutional culture focused on excellence and results.